Pregnancy and Oral Health - Loncar, Stefan D; Loncar, Dragan; Nestorovic, Ana; Supljeglav, Igor (Medicinski časopis, 2014)
Introduction: Pregnancy is a period of life when dental care needs to be taken to the next level. Objective: The research objective is to indicate the presence of risk factors for oral disease through tracking the oral hygiene habits among the examined pregnant women. Method: The study included 45 pregnant women with gestational age of 8th-38th gestational week that corresponded to the questionnaire in the field of habits in oral hygiene. The obtained data were statistically processed using a percentage calculation after the logical processing of answers. Results: 80% of the total number of pregnant women examined maintains oral hygiene, out of which 64% use only basic remedies and remaining 36% are using some of the additional remedies (different types of mouthwash, dental floss or interdental brushes). Even 69% of women examined goes to the dentist only when necessary that is only when a problem occurs (pain, swelling). Habit of teeth brushing immediately after vomiting is found with 69% of women examined. All pregnant women up to 45% take less than three minutes a day to maintain oral hygiene. Approximately 60% of the women examined noticed gum bleeding while teeth brushing during pregnancy. Out of total pregnant women examined, 27% confirmed to have taken less attention to oral health during pregnancy. Only 60% of women examined are informed about the importance of oral health during pregnancy and 40% of them have not been informed of importance of oral health. Conclusion: There should be a continuous process of application of prophylactic and therapeutic, as well as educational and health procedures, in dealing with pregnant women. When it comes to maintaining oral health, it is vital to inform pregnant women about comprehensible and practically applicable advice that will improve their awareness of the importance of oral hygiene.Key words: Oral health, pregnancy, prevention